Global IR and the middle power concept: exploring different paths to agency - Efstathopoulos, Charalampos (Australian journal of international affairs, 2023)
The premise of Global IR for greater pluralism and inclusivity allows for reconsidering the relevance of established concepts in the IR discipline. This article discusses how Global IR can contribute to rethinking the question of agency in the middle power concept. While the concept has been used in a Western and non-Western context, there is a tendency to adopt a binary distinction between Western middle powers that are conformist in their approach to the liberal international order and Southern middle powers that adopt a reformist stance. The article argues that a Global IR approach can help overcome this dichotomy and open up the study of Western and Southern middle powers to new agential possibilities. To demonstrate this, the article discusses how the cases of Australia and Brazil are not limited to conformist and reformist middle power agencies respectively. The discussion shows how the two states have undergone periods of ambivalence to gradually project new forms of middle power agency that alter and redefine their roles within the liberal international order.